Frequency-tuned contactless conductivity detector for the electrophoretic separation of clinical samples in capillaries with very small internal dimensions - Tůma, Petr (Journal of separation science, 2017)
An axial design of a capacitively coupled contactless conductivity detector was tested in combination with fused-silica capillaries with internal diameters of 10, 15, and 25 μm, which are used for high-efficiency electrophoretic separation. The transmission of the signal in the detection probe dependent on the specific conductivity of the solution in the capillary in the range 0-278 mS.m-1 has a complex character and a minimum appears on the curve at very low conductivities. The position of the minimum of the calibration dependence gradually shifts with decreasing frequency of the exciting signal from 1.0 to 0.25 MHz toward lower specific conductivity values. The presence of a minimum on the calibration curves is a natural property of the axial design of contactless conductivity detector, demonstrated by solution of the equivalent electrical circuit of the detection probe, and is specifically caused by the use of shielding foil. The behavior of contactless conductivity detector in the vicinity of the minimum was documented for practical separations of amino acids in solutions of 3.2 M acetic acid with addition of 0-50% v/v methanol.
Keywords: contactless conductivity detection; elektrická vodivost; clinical analysis; frequency optimization; Calibration; Electrophoresis, Capillary; elektroforéza kapilární; Electric Conductivity; aminokyseliny; kalibrace; capillary electrophoresis; simulation; Amino Acids